Book Review: M. HESLOP, Medieval Greece: encounters between Latins, Greeks and others in the Dodecanese and the Mani [ser. Variorum Collected Studies]; foreword by Jonathan HARRIS [xvi-xviii] (London & New York: Routledge-Francis & Taylor Group, 2021) - ΠΕΡΡΑ ΦΩΤΕΙΝΗ Β. (Byzantina Symmeikta, 2021)
M. Heslop, Medieval Greece: encounters between Latins, Greeks and others in the Dodecanese and the Mani [ser. Variorum Collected Studies]; foreword by Jonathan HARRIS [xvi-xviii] (London & New York: Routledge-Francis & Taylor Group, 2021)